Um olhar freireano para o processo de construção de atividades de ensino a partir da pergunta dos estudantes sobre petróleo - Oliveira, Thaís Andressa Lopes de (2018)
This research is based on the presuppositions of Freirean didactics, with emphasis on the notions of dialogue, curiosity, pedagogy of the question and generating themes. This research aimed to understand how students' questions about a given topic can contribute to the elaboration and application of teaching activities. This qualitative research is a case study type. The participants were 134 students from the 3rd grade of High School and the teacher responsible for the classes in which the intervention that constituted this case in question occurred. The students were been invited to ask questions about what they would like to know about Oil. Based on more than 400 questions, a sequence of activities were build based on the Jigsaw Method of Cooperative Learning that made it possible to work on the theme comprehensively. In this context, the data collection for this research was been done by means of the survey of the students' questions, complemented by the diary of the researcher, and by the application of questionnaires with the former students and the teacher. The analysis of the obtained data were been made by using the Discursive Textual Analysis method (MORAES; GALIAZZI, 2013). The analysis of the questions revealed that the choices made during the planning process were consistent, since the focus of interest of the students was included in the proposed activities, helping them to reformulate their initial conceptions on the theme. The questionnaires, in turn, revealed the acceptance of the proposal by the students and the class teacher, as it contributed to learning, aroused interest, improved the relationship between the students and the teacher in the classroom, and fostered in the students the taste for research. It is expected, therefore, that this research can contribute to teacher education, as well as the recognition of the role students' questions play in the teaching and learning process, and the potentialities of asking questions to construct teaching activities